KEBEBASAN BERAGAMA DALAM PERSPEKTIF ABDURRAHMAN WAHID - Damrizal Damrizal (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2016)
Abstract: Violence in the name of religion over the past decades continues to rise. Not only conflict involving inter-religious,  but also occurs in internal  religious  communities that  exist in Indonesia. The recognition  of absolute truth (truth claims)  in the propagation of religion, or a unilateral claim to the most  correct opinion, assuming the other is wrong, in interpreting the sacred text of a religion is the seeds that at any moment can trigger the outbreak of the conflict. Awareness of nationality,  including  the reality of plurality, which  framed the  Unitary Republic  of Indonesia based on Pancasila continue to be  degraded in the  midst  of society  that can  no longer  be  a unifying pillar. The conditions there  should  be  a serious  concern by all parties  in order to reduce collisions  that occur  in the community because of their difference in value or the existing norms. Few people pay attention to this issue  is one  of them,  Abdurrahman Wahid.  As a former  NU chairman and former president, Abdurrahman Wahid, known  as the protector of minorities, as part of its implementation in maintaining freedom. It is interesting to know  what  you think Abdurrahman Wahid  on religious freedom. In this study, researchers used a qualitative approach. The method in analyzing the data with descriptive analysis, a method that addresses the issue  by presenting findings from the research subjects to get a conclusion on the basis of theoretical studies that have been done  before.  Techniques of collecting  data is with the research literature, namely  the search for materials in the form of books, articles freelance or search the data by using the internet.  The results of this study show religious freedom offered Abdurrahman Wahid is a consciousness that  recognizes the  diversity of Muslims and  human diversity. Where  each  religion run sound  belief.  Islam as a religion of grace  lil Alamin applied  in real life, in which  every citizen has the right to show  their identity without  any discrimination of any party. Understanding the implications of Religious Freedom was  initiated by Abdurrahman Wahid  Dapa felt by religious communities in Indonesia today. When  religious people can coexist  harmoniously and peacefully. Even against marginalized religious groups  such  as Shiite, Ahamadiyah and Confucian.  Even Confucian  become a religion of its own in the era of its leadership and make the Lunar day as a national  holiday, as the implications of religious freedom that he woke  up.